Revealing factors influencing the operational stability of perovskite light-emitting diodes - Warby, JH; Wenger, B; Ramadan, AJ; Oliver, RDJ; Sansom, HC; Marshall, AR; Snaith, HJ (American Chemical Society, 2020)
Light-emitting diodes (LEDs) made from metal halide perovskites have demonstrated external electroluminescent quantum efficiencies (EQEEL) in excess of 20%. However, their poor operational stability, resulting in lifetimes of only tens to hundreds of hours, needs to be dramatically improved prior to commercial use. There is little consensus in the community upon which factors limit the stability of these devices. Here, we investigate the role played by ammonium cations on the operational stability. We vary the amount of phenylethylammonium bromide, a widely used alkylammonium salt, that we add to a precursor solution of CsPbBr3 and track changes in stability and EQEEL. We find that while phenylethylammonium bromide is beneficial in achieving high efficiency, it is highly detrimental to operational stability. We investigate material properties and electronic characteristics before and after degradation and find that both a reduction in the radiative efficiency of the emitter and significant changes in current–voltage characteristics explain the orders of magnitude drop in the EQEEL, which we attribute to increased ionic mobility. Our results suggest that engineering new contacts and further investigation into materials with lower ionic mobility should yield much improved stability of perovskite LEDs.